Use of rat hepatocytes immobilized in agarose gel threads for biosynthesis of metabolites of potential cytostatics - Trejtnar, F; Skálová, L; Szotáková, B; Wsól, V (Experimental and toxicologic pathology, 1999)
The aim of this work was to evaluate possibility of use of the rat isolated hepatocytes immobilized in agarose gel and continuously perfused for production of needed metabolites of two potential cytostatics, benfluron (5-(2-dimethylamino-ethoxy)-7-oxo-7H-benzo[c]fluorene) and oracin (6-[2-(hydroxyethyl) amino-ethyl]-5,11-dioxo-5,6-dihydro-11H-indeno [1,2-c]isoquinoline). The rat isolated hepatocytes obtained by two-step collagenase perfusion method were immobilized in agarose threads and perfused in a small bioreactor under a recirculation regimes. Biosynthesis of 9-hydroxybenfluron and 3-hydroxyoracin in immobilized rat hepatocytes was studied. Yields of the metabolites of interest in hepatocytes in immobilized and perfused rat hepatocytes was compared to production of metabolites in hepatocyte suspension and in rats in vivo. 9-hydroxybenfluron was presented during perfusion of immobilized rat hepatocytes in a relatively high amounts but total recovery all forms of benfluron was very low due to especially high binding to components of the perfusion system. More effective method remains the production of 9-hydroxybenfluron in rats in vivo. A considerable biosynthesis of 3-hydroxyoracin by immobilized rat hepatocytes in the bioreactor was found. Concentration of the metabolite in the perfusate rose continuously during 6 hours of perfusion. 3-hydroxyoracin production was increased several times with use of immobilized hepatocytes from rats treated for three days with methylcholanthrene. The yield of 3-hydroxyoracin in rats in vivo was comparably high but an advantage of in vitro synthesis is a much shorter interval to obtain the same amount of the metabolite of interest. In spite of some limitations in compounds exerting high trapping in the perfusion system, the method of the immobilized and perfused hepatocytes can be very useful and effective for production of some drug metabolites in biochemistry and pharmacology.
Keywords: sefarosa; Male; Perfusion; Rats, Wistar; ethanolaminy; protinádorové látky; Hydroxylation; Bioreactors; hydroxylace; Ethanolamines; Methylcholanthrene; fluoreny; mužské pohlaví; potkani Wistar; bioreaktory; Fluorenes; krysa rodu Rattus; Animals; játra; Sepharose; isochinoliny; methylcholanthren; zvířata; Rats; perfuze; Isoquinolines; Liver; Antineoplastic Agents